2004
DOI: 10.1111/j.1365-294x.2004.02365.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological and life history characteristics predict population genetic divergence of two salmonids in the same landscape

Abstract: Ecological and life history characteristics such as population size, dispersal pattern, and mating system mediate the influence of genetic drift and gene flow on population subdivision. Bull trout (Salvelinus confluentus) and mountain whitefish (Prosopium williamsoni) differ markedly in spawning location, population size and mating system. Based on these differences, we predicted that bull trout would have reduced genetic variation within and greater differentiation among populations compared with mountain whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(114 citation statements)
references
References 100 publications
6
105
3
Order By: Relevance
“…Species and landscape interaction cannot be limited to the landscape perspective as inherent peculiarities across species influence varying response patterns to the same landscape effects. It is also important to examine inherent variations among species as those that are intrinsically different but share a common landscape may either show similar patterns of interaction with the landscape (e.g., Gagnon & Angers, 2006; Petren, Grant, Grant, & Keller, 2005) or respond uniquely and exhibit distinct patterns despite a shared habitat (e.g., Short & Caterino, 2009; Whiteley, Spruell, & Allendorf, 2004). Thus, a species‐centered comparative approach in conducting landscape genetic studies will refine previous generalizations and will avoid casual association of species with a generic roster of dispersal corridors and landscape barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Species and landscape interaction cannot be limited to the landscape perspective as inherent peculiarities across species influence varying response patterns to the same landscape effects. It is also important to examine inherent variations among species as those that are intrinsically different but share a common landscape may either show similar patterns of interaction with the landscape (e.g., Gagnon & Angers, 2006; Petren, Grant, Grant, & Keller, 2005) or respond uniquely and exhibit distinct patterns despite a shared habitat (e.g., Short & Caterino, 2009; Whiteley, Spruell, & Allendorf, 2004). Thus, a species‐centered comparative approach in conducting landscape genetic studies will refine previous generalizations and will avoid casual association of species with a generic roster of dispersal corridors and landscape barriers.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in population structuring has been attributed to species differences in spawning ecology, dispersal potential and effective population size (Castric and Bernatchez 2004;Whiteley et al 2004). Considering these factors, black redhorse are not likely to show strong population structure within watersheds.…”
Section: Population Genetic Structurementioning
confidence: 98%
“…Previous research using this experimental design found predictable patterns of genetic variation of fish and invertebrate species in watersheds on the basis of their ability to ascend stream gradients and migrate over long distances (Monaghan et al 2002;Whiteley et al 2004;de Kerckhove 2005). Another promising approach would be the study of the same organism in different landscape arrangements (e.g., Castric et al 2001).…”
Section: Discussionmentioning
confidence: 99%